2016
DOI: 10.1007/978-3-319-45559-4_6
|View full text |Cite
|
Sign up to set email alerts
|

Applying ER-MCDA and BF-TOPSIS to Decide on Effectiveness of Torrent Protection

Abstract: International audienceExperts take into account several criteria to assess the effectiveness of torrential flood protection systems. In practice, scoring each criterion is imperfect. Each system is assessed choosing a qualitative class of effectiveness among several such classes (high, medium, low, no). Evidential Reasoning for Multi-Criteria Decision-Analysis (ER-MCDA) approach can help formalize this Multi-Criteria Decision-Making (MCDM) problem but only provides a coarse ranking of all systems. The recent B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The analysis of each decision-making problem depends on the analysis of several criteria of which the assessment is imperfect and performed in an uncertain environment. Decision-aiding methods grounded on Evidential Reasoning as previously introduced are used to answer each of these problems (Carladous et al, 2015(Carladous et al, , 2016c, as shown in Fig. 9.…”
Section: Stage 3: Decision-aiding Methods For Each Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of each decision-making problem depends on the analysis of several criteria of which the assessment is imperfect and performed in an uncertain environment. Decision-aiding methods grounded on Evidential Reasoning as previously introduced are used to answer each of these problems (Carladous et al, 2015(Carladous et al, , 2016c, as shown in Fig. 9.…”
Section: Stage 3: Decision-aiding Methods For Each Problemmentioning
confidence: 99%
“…The objective of this article is to show how the use of new decisionaiding methods may be integrated into a formalised framework of analysis through the conceptual description of this analytical framework. This article does not aim at detailing mathematical aspects of such methods or at showing the real application of these individual methods on different sub-problems as already done elsewhere (Carladous et al, 2015(Carladous et al, , 2016c. Under this assumption, the Section 2 introduces the methods, didactically, without detailing calculation-intensive aspects but by justifying choices made.…”
Section: A Multi-scale Multi-component Decision-making Problem Based ...mentioning
confidence: 99%
“…As shown in this application example, our proposed distance measure can be well used in the multiple criterion decision making. d E BI has also been used successfully in other kind of applications related to risk management and for protecting housing areas against torrential floods in France [46], [47].…”
Section: K Application Of D E Bi In Multiple Criteria Decision Makingmentioning
confidence: 99%